A case of culture-negative endocarditis due to Streptococcus tigurinus. Issue 2 (February 2015) - Kanamori, Hajime; Kakuta, Risako; Yano, Hisakazu; Suzuki, Tomoyuki; Gu, Yoshiaki; Oe, Chihiro; Inomata, Shinya; Aoyagi, Tetsuji; Hatta, Masumitsu; Endo, Shiro; Tokuda, Koichi; Weber, David J.; et al.
Abstract Culture-negative endocarditis remains a diagnostic and therapeutic challenge despite recent medical advances. Streptococcus tigurinus, a novel member of the Streptococcus mitis group, was first identified in Zurich. S. tigurinus possesses virulence determinants and causes invasive infections. We report a case of culture-negative endocarditis with serious complications due to S. tigurinus, which was identified by 16S ribosomal RNA gene sequence analysis of excised valve tissue specimens. This technique is useful for identification of the causative microorganism in patients with culture-negative endocarditis and may facilitate early diagnosis and appropriate antimicrobial treatment.